1999
DOI: 10.1002/(sici)1520-6866(1999)19:1<33::aid-tcm4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocarcinogenic activity of N-butyl-N-(4-hydroxybutyl)nitrosamine in rats is not modified by sodium l-ascorbate

Abstract: Male F344 and Wistar Shionogi (WS) rats were treated with 0.05% N‐butyl‐N‐(4‐hydroxybutyl)nitrosamine (BBN) for 20 weeks and then killed at week 36 (experiment 1). Although reduction of body weight increase was found, no effects on liver weights were noted. Formalin‐fixed and paraffin‐embedded liver tissues from rats killed terminally were cut and stained for glutathione S‐transferase placental form (GST‐P) immunohistochemically. Marked elevation of quantitative values of small GST‐P positive (GST‐P+) foci wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Sodium ascorbate also did not affect the development of PGST‐positive foci induced by DEN 145. In rats administered 0.05% N ‐butyl‐ N ‐(4‐hydroxybutyl)nitrosamine, feeding 5% sodium ascorbate did not affect the development of altered hepatic foci 146. In rats receiving kojic acid as a tumor promoting agent, Takabatake et al .…”
Section: Vitamin Cmentioning
confidence: 97%
“…Sodium ascorbate also did not affect the development of PGST‐positive foci induced by DEN 145. In rats administered 0.05% N ‐butyl‐ N ‐(4‐hydroxybutyl)nitrosamine, feeding 5% sodium ascorbate did not affect the development of altered hepatic foci 146. In rats receiving kojic acid as a tumor promoting agent, Takabatake et al .…”
Section: Vitamin Cmentioning
confidence: 97%
“…8,10,35) Recently, quantitative data for GST-P-positive foci comprising very small numbers of hepatocytes have been used for detection of liver carcinogens and assessment of hepatocarcinogenic risk. 11,17,32,36) It has been demonstrated that levels of MeIQx-DNA adducts linearly increase from very low doses, but this is not the case for GST-P-positive foci development. 11,17) Our present data also demonstrated that maternal exposure to MeIQx during the period of pregnancy and lactation did not increase the number of GST-P-positive foci in the liver despite causing genetic damage.…”
Section: Meiqx Treatmentmentioning
confidence: 99%